Distinctive left-sided distribution of adrenergic-derived cells in the adult mouse heart. - Kingsley Osuala; Kathleen Telusma; Saad M Khan; Shandong Wu; Mubarak Shah; Candice Baker; Sabikha Alam; Ibrahim Abukenda; Aura Fuentes; Hani B Seifein; Steven N Ebert (PLoS ONE, 2011)
Adrenaline and noradrenaline are produced within the heart from neuronal and non-neuronal sources. These adrenergic hormones have profound effects on cardiovascular development and function, yet relatively little information is available about the specific tissue distribution of adrenergic cells within the adult heart. The purpose of the present study was to define the anatomical localization of cells derived from an adrenergic lineage within the adult heart. To accomplish this, we performed genetic fate-mapping experiments where mice with the cre-recombinase (Cre) gene inserted into the phenylethanolamine-n-methyltransferase (Pnmt) locus were cross-mated with homozygous Rosa26 reporter (R26R) mice. Because Pnmt serves as a marker gene for adrenergic cells, offspring from these matings express the β-galactosidase (βGAL) reporter gene in cells of an adrenergic lineage. βGAL expression was found throughout the adult mouse heart, but was predominantly (89%) located in the left atrium (LA) and ventricle (LV) (p<0.001 compared to RA and RV), where many of these cells appeared to have cardiomyocyte-like morphological and structural characteristics. The staining pattern in the LA was diffuse, but the LV free wall displayed intermittent non-random staining that extended from the apex to the base of the heart, including heavy staining of the anterior papillary muscle along its perimeter. Three-dimensional computer-aided reconstruction of XGAL+ staining revealed distribution throughout the LA and LV, with specific finger-like projections apparent near the mid and apical regions of the LV free wall. These data indicate that adrenergic-derived cells display distinctive left-sided distribution patterns in the adult mouse heart.